Surprises, Grumpy Old Men, and Immigrant Secrets: Migration in Short Stories - Sevgi, Mehmet Ali (Migration Letters, 2024)
This ethnographic study, conducted among Turkish immigrants in Germany between 2012 and 2016, aims to reveal the personal migration stories of the participants based on materials obtained through interviews and participant observation. In this context; topics, immigrant experiences, and life stories collected in the field with ethnographic research techniques are conveyed in a literary manner through short stories. Ethnographic journals accompanying the short stories include methodological discussions such as anthropologists’ use of literature and the place of fiction in ethnographic writing. Possible migration-based discussions that may arise with short stories are discussed together with some basic concepts in social sciences by making references to the stories. In this context, this study aims to address the issue of immigration as the personal story of the immigrant and is an effort to reveal its own discussion texts in its own distinctive structure.